STUDENTS’ PERCEPTION OF ONLINE LEARNING IN UNIVERSITY OF DAYANU IKHSANUDDIN BAUBAU - Nining Syafitri; Nur Melansari (English Education Journal, 2021)
The problem statements of this research were: 1) what effect did the instructional design and delivery of English course to the student satisfaction?; 2) what impact did lecturer roles have on the student satisfaction, including feedback and assessment?; 3) what student duties and responsibilities were critical for a pleasant online class experience?; and 4) how effective were the management and support systems at delivering services when they are required? The method of the research used a quantitative approach by using survey method. The results of the research were: 1) the effects of the instructional design and delivery of English course to the student satisfaction were during English online class, the students were given chances to use materials from various sources and to interact each other virtually; 2) the impacts of lecturer roles had on the student satisfaction, including feedback and assessment were important, especially by providing various contents and sources of materials, help students in overcoming learning problems, feedback and assessment; 3) student duties and responsibilities were important, including motivation and interaction in joining English online class; and 4) the management and support systems were generally effective at delivering services when they were required.